2014
DOI: 10.1186/1476-069x-13-105
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution events from forest fires and emergency department attendances in Sydney, Australia 1996–2007: a case-crossover analysis

Abstract: BackgroundSevere air pollution generated by forest fires is becoming an increasingly frequent public health management problem. We measured the association between forest fire smoke events and hospital emergency department (ED) attendances in Sydney from 1996–2007.MethodsA smoke event occurred when forest fires caused the daily citywide average concentration of particulate matter (PM10 or PM2.5) to exceed the 99th percentile of the entire study period. We used a time-stratified case-crossover design and condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 35 publications
(50 reference statements)
4
98
0
3
Order By: Relevance
“…A validated database used to distinguish days with high pollution resulting from LFS was used in two Sydney‐based studies to characterize the impacts of specific ‘event’ days rather than incremental pollutant increases . Studies which compared impacts of background airborne particulate matter (PM) to that arising from fires (PM LFS ) found the latter to be associated with higher respiratory risk estimates, raising the potential for a differing or greater magnitude of cellular responses arising from the specific chemical composition unique to the particles in LFS.…”
Section: Respiratory Impactsmentioning
confidence: 99%
“…A validated database used to distinguish days with high pollution resulting from LFS was used in two Sydney‐based studies to characterize the impacts of specific ‘event’ days rather than incremental pollutant increases . Studies which compared impacts of background airborne particulate matter (PM) to that arising from fires (PM LFS ) found the latter to be associated with higher respiratory risk estimates, raising the potential for a differing or greater magnitude of cellular responses arising from the specific chemical composition unique to the particles in LFS.…”
Section: Respiratory Impactsmentioning
confidence: 99%
“…A national study showed via principal component analyses that several vulnerability factors similar to those for general air pollution were relevant for fire-PM 2.5 ; specifically, factors included age (e.g., those >65 years); adults with respiratory disease (e.g., COPD and asthma); adults with hypertension, obesity and diabetes; children with asthma; and economic deprivation [35]. Age may also be a factor contributing to a population's susceptibility [36][37][38][39][40].…”
mentioning
confidence: 99%
“…These fires can be intense enough to create pyro-convective lofting and inject smoke at high altitudes (Fromm et al, 2006;Dirksen et al, 2009;Guan et al, 2010) and are expected to become more frequent under a 15 changing climate (Bradstock et al, 2009;Cai et al, 2009;Keywood et al, 2013;King et al, 2013). There has been growing interest in characterising the composition of smoke from Australian temperate forest fires in recent years, mostly arising from increased awareness of the significant impacts of bushfire smoke on regional air quality (Reisen et al, 2011(Reisen et al, , 2013Price et al, 2012;Keywood et al, 2015;Rea et al, 2016) and its associated repercussions on human health (Reisen and Brown, 2006;Johnston et al, 2012Johnston et al, , 2014Reisen et al, 2015;Reid et al, 2016), coincident with a mandate for state agencies to increase 20 prescribed burning in the wake of the catastrophic 2009 forest fires in Victoria (Teague et al, 2010). Prescribed burning is widely used in Australia as a means of reducing bushfire risk (Boer et al, 2009); however, these low to moderate intensity fires often take place close to population centres, under weather conditions that are conducive to pollution build up, sometimes on a regional scale (e.g., Williamson et al, 2016, Fig.…”
Section: Introductionmentioning
confidence: 99%